Church Archaeology in Transylvania (ca. 950 to ca. 1450) - Istrate, Daniela Marcu, author.
1 online resource.
Keywords: Transylvania has some of the most valuable monuments of medieval architecture in Europe. The oldest church was built in the 10th century, but most others came into being only after 1200. Later changes have considerably modified the appearance of still-standing buildings. Written sources are lacking for answers to questions about the identity of the builders and patrons. Countering the idea that only standing structures can reflect the history of medieval churches in Transylvania, this book uses archaeological sources in order to answer some of those questions and to bring to light the hidden past of many monuments.